2009
DOI: 10.1152/ajpendo.90531.2008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α upregulates 11β-hydroxysteroid dehydrogenase type 1 expression by CCAAT/enhancer binding protein-β in HepG2 cells

Abstract: The enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) catalyzes the conversion of inactive to active glucocorticoids. 11β-HSD1 plays a crucial role in the pathogenesis of obesity and controls glucocorticoid actions in inflammation. Several studies have demonstrated that TNF-α increases 11β-HSD1 mRNA and activity in various cell models. Here, we demonstrate that mRNA and activity of 11β-HSD1 is increased in liver tissue from transgenic mice overexpressing TNF-α, indicating that this effect also occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 63 publications
3
41
0
Order By: Relevance
“…Thus, time-course studies after UNX in the remaining kidney must be performed in order to identify relevant regulatory factors for the expression of 11b-HSD1 and 11b-HSD2. A number of factors regulating the expression of 11b-HSD enzymes have previously been identified including TNF-a, Erg1, NF-kB, NF1, C/EBPs, GR, Sp1/Sp3, Arnt, PPAR-a/PPAR-g, IL1, glucocorticoids, sex steroids, and thyroid hormones (Alikhani-Koopaei et al 2004, Tomlinson et al 2004, Kostadinova et al 2005, Alikhani-Koupaei et al 2007, Wake et al 2007, Ignatova et al 2009). The ultimate proof for a pivotal relevance of one or a combination of these factors would require the investigation of animals with specific over-or under-expression in the cortical collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, time-course studies after UNX in the remaining kidney must be performed in order to identify relevant regulatory factors for the expression of 11b-HSD1 and 11b-HSD2. A number of factors regulating the expression of 11b-HSD enzymes have previously been identified including TNF-a, Erg1, NF-kB, NF1, C/EBPs, GR, Sp1/Sp3, Arnt, PPAR-a/PPAR-g, IL1, glucocorticoids, sex steroids, and thyroid hormones (Alikhani-Koopaei et al 2004, Tomlinson et al 2004, Kostadinova et al 2005, Alikhani-Koupaei et al 2007, Wake et al 2007, Ignatova et al 2009). The ultimate proof for a pivotal relevance of one or a combination of these factors would require the investigation of animals with specific over-or under-expression in the cortical collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the activities of HSD11B1 and HSD11B2 enzymes by different endogenous molecules, xenobiotics, and in various disease states has been described previously; it appears to be clinically relevant (Escher et al 1997, 1998a,b, Fuster et al 1998, Quattropani et al 2001, Heiniger et al 2003, Kostadinova et al 2005, Ignatova et al 2009, Konopelska et al 2009). Herein, we report a novel player, 27-OHC, which regulates the activity of these key enzymes, thereby determining the intracellular availability of glucocorticoids.…”
Section: Discussionmentioning
confidence: 74%
“…With the ultimate goal of treating and/or preventing the metabolic syndrome, an array of exogenous compounds inhibiting the activity of HSD11B1 have been synthesised (Boyle & Kowalski 2009), and the role of endogenous compounds including insulin, glucocorticoids, TNFa, and bile acids and their molecular mechanisms in the regulation of the expression and activity of HSD11B have been reported (Escher et al 1997, Ackermann et al 1999, Williams et al 2000, Quattropani et al 2001, Kostadinova et al 2005, Balachandran et al 2008, Ignatova et al 2009). Thus, understanding the factors regulating the activity of this enzyme is of potential clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Although 11b-HSD1 expression also plays an important role in the development of metabolic syndromes, in recent years pharmacological interventions targeting 11b-HSD1 have mainly focused on the inhibition of 11b-HSD1 enzymatic activity. Several stimuli, including HG, TNF-a, and lipopolysaccharide (LPS) have been shown to stimulate the expression of 11b-HSD1 in different cells (Ishii et al 2007, Ignatova et al 2009, Fan et al 2011. It has been reported that TNF-a-induced 11b-HSD1 expression was mediated by p38 MAPK, CCAAT/ enhancer binding protein (C/EBP)-b, and NF-kB pathways (Ignatova et al 2009).…”
Section: Figurementioning
confidence: 99%